Inconclusive effects between executive functions and symptoms of psychiatric disorders in random-intercept cross-lagged panel models: a simulated reanalysis and comment on Halse et al. (2022) - Sorjonen, Kimmo; Melin, Bo (Frontiers in Psychology, 2025)
BackgroundIn a recent study of Norwegian children (N = 874), Halse et al. used random-intercept cross-lagged panel models (RI-CLPM) and concluded that their findings supported the assumption that deficiencies in executive functions and psychopathology are both a cause and a consequence of the other. However, it is known that RI-CLPM can give biased results.MethodsWe reanalyzed data simulated to resemble the data used by Halse et al. with several complementary models, e.g., latent change score models (LCSM).ResultsThe analyzed models indicated contradictory simultaneous increasing and decreasing effects between executive deficits and symptoms of psychopathology.ConclusionThe present contradictory findings suggested that prospective effects between executive deficits and symptoms of psychopathology may have been spurious rather than truly increasing. Consequently, conclusions by Halse et al. appear to have been premature. It is important for researchers to bear in mind that correlations, including cross-lagged effects in RI-CLPM, do not prove causality. Careful interpretation of RI-CLPM results is of utmost importance in, for example, research in clinical and developmental psychology. We recommend researchers to use, as we did here, triangulation to scrutinize findings from analyses of observational data.